My body, my self for boys : the "what's happening to my body" workbook - Madaras, Lynda; Madaras, Area. (New York : New Market Press, 2000)
Explanatory text and workbook exercises present information about such aspects of male puberty as penis size, masturbation, and acne.
"The 'What's happening to my body?' workbook."
Includes bibliographical references (p. 93).
Keywords: Teenage boys -- Growth -- Juvenile literature; Teenage boys -- Physiology -- Juvenile literature; Puberty -- Juvenile literature; Sex instruction for boys -- Juvenile literature